Unsteady Hydromagnetic Mixed Convection of a Radiating and Reacting Nanofluid in a Microchannel with Variable Properties - KEFENE, Mesfin Zewde; MAKINDE, Oluwole Daniel; ENYADENE, Lemi Guta (Engineering Transactions, 2023)
Unsteady MHD mixed convection of nanofluid heat transfer in a permeable microchannel with temperature-dependent fluid properties is studied under the influence of a first-order chemical reaction and thermal radiation. The viscosity and thermal conductivity are assumed to be related to temperature exponentially. Using suitable dimensionless variables and parameters, the governing partial differential equations (PDEs) are transformed to their corresponding dimensionless forms solved numerically by a semi-discretization finite difference scheme along with the Runge-Kutta-Fehlberg integration technique. The effects of model parameters on the profiles of velocity, temperature, concentration, skin friction, the Nusselt number, and the Sherwood number are discussed qualitatively with the aid of graph.